Flipped Classroom and Reflective Practice for Active Learning during Online Class: An Experience in Engineering Drawing Module - Wangi Pandan Sari; Angelica Helen Saputro; Tari Hardiani Safitri (Journal of Educational Science and Technology (EST), 2023)
A flipped classroom is a pedagogical approach that reverses the traditional model of learning where students are provided with materials prior to class. Whereas reflective practice is an approach that encourages students to analyze their learning experiences and evaluate their progress in understanding course materials. The COVID-19 pandemic has challenged the traditional model of classroom instruction, leading to a shift in teaching and learning activities toward virtual/remote delivery methods. This study evaluates the flipped classroom approach and reflective practices in Engineering Drawing module. The participants consisted of first year engineering students (n=76). The result fo the study shows positive outcomes from using flipped learning and reflective practice. Students felt that the module provided them with an engaging and challenging learning experience, enhancing not only their technical skills but also their overall learning capabilities